Sphenotrochus cairnsi, new name for Sphenotrochus cuneolus Cairns 2004 (Scleractinia: Turbinoliidae) - Garberoglio, Ricardo M. (Zootaxa, 2018)
S.D. Cairns (2004) described the solitary Recent Scleractinia species Sphenotrochus cuneolus (p. 299, figs. 9A-F) from Marion Plateau (Queensland, Australia) and Sulu Archipelago (Philippines), but that name had already been used for a coral from the Eocene of Belgium (in Vincent & Lefevre 1872, p. 68, pl. 3, fig. 9). The same name appears in a figure (pl. 1, fig. 11) from Couffon (1903) on the Miocene of France, but it is clearly a mistake, since in the description of the species (p. 89) he mentions Turbinolia cuneolus, a species descripted by Michelin (1840–1847; p. 287, pl. 66, fig. 2).